The Influence of Leadership and Achievement Motivation on Employee Performance Through Job Satisfaction as a Mediator at PT. BPR Picu Manunggal Sejahtera - PUTRA, I Made Oka Pratama; DHARMANEGARA, Ida Bagus Agung; AMERTHA, I Made Suniasta (PT Keberlanjutan Strategis Indonesia, 2024)
The purpose of this research is to analyze the influence of leadership and achievement motivation on employee performance with job satisfaction as a mediating variable at PT. BPR Triggers Manunggal Sejahtera. The method used in the research is quantitative with a questionnaire carried out systematically in accordance with the research objectives. The population in this study were all employees at PT. BPR Picu Manunggal Sejahtera except for 30 leaders. This research was analyzed using PLS-based SEM. The research results show that (1) Leadership has a positive and insignificant effect on job satisfaction at PT. BPR Picu Manungal Sejahtera (2) Leadership has a positive but not significant effect on employee performance at PT. BPR Picu Manunggal (3) Achievement motivation has a positive and significant effect on job satisfaction at PT. BPR Picu Manunggal Sejahtera (4) Achievement motivation has a positive and significant effect on employee performance at PT. BPR Picu Manunggal Sejahtera (5) Job satisfaction has a positive and insignificant effect on employee performance at PT. BPR Triggers Manunggal Sejahtera. This means that the better the job satisfaction provided, the employee performance will increase (6) Satisfaction mediates the influence of leadership on employee performance (7) Satisfaction does not mediate the influence of achievement motivation on employee performance. It is recommended that future researchers add alternative constructs that influence employee performance such as work environment, job training, compensation, communication, etc. as well as increase references related to research.